LCâUV/MS quality analytics of paediatric artemether formulations - Kirsten Vandercruyssen; Matthias DâHondt; Valentijn Vergote; Herwig Jansen; Christian Burvenich; Bart De Spiegeleer (Elsevier, 2014)
A highly selective and stability-indicating HPLC-method, combined with appropriate sample preparation steps, is developed for Î²-artemether assay and profiling of related impurities, including possible degradants, in a complex powder for oral suspension. Following HPLC conditions allowed the required selectivity: a Prevail organic acid (OA) column (250Â mmÃ4.6Â mm, 5Â Î¼m), flow rate set at 1.5Â mL/min combined with a linear gradient (where A=25Â mM phosphate buffer (pH 2.5), and B=acetonitrile) from 30% to 75% B in a runtime of 60Â min. Quantitative UV-detection was performed at 210Â nm. Acetonitrile was applied as extraction solvent for sample preparation. Using acetonitrileâwater mixtures as extraction solvent, a compartmental behaviour by a non-solving excipient-bound fraction and an artemether-solubilising free fraction of solvent was demonstrated, making a mobile phase based extraction not a good choice. Method validation showed that the developed HPLC-method is considered to be suitable for its intended regulatory stability-quality characterisation of Î²-artemether paediatric formulations. Furthermore, LCâMS on references as well as on stability samples was performed allowing identity confirmation of the Î²-artemether related impurities. MS-fragmentation scheme of Î²-artemether and its related substances is proposed, explaining the m/z values of the in-source fragments obtained. Keywords: Paediatric formulations, Sample preparation, Polar embedded organic acid column, Artemisinin trioxane derivatives, Related impurities and degradation compounds, MS-fragmentation